Preparation method of tungsten oxide rod deposition gold particle coated cadmium sulfide for selective photocatalytic oxidation of benzyl alcohol for hydrogen evolution
By depositing gold nanoparticles on WO2.72 nanorods and coating cadmium sulfide layer to form WO2.72-Au/CdS composite material, the problem of dependence on ultraviolet light of traditional photocatalytic materials is solved, and the effective utilization of visible and near-infrared light is achieved, which significantly improves photocatalytic activity and selectivity.
Patent Information
- Application Number
- CN202411868288.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional semiconductor-driven photocatalytic reactions are limited by being able to be excited only by ultraviolet light, and their photocatalytic activity is insufficient, making it impossible to effectively utilize visible and near-infrared light.
By depositing gold (Au) nanoparticles at the tip of WO2.72 nanorods and covering a thin layer of cadmium sulfide (CdS) on their surface, WO2.72-Au/CdS composite material is formed to enhance its local surface plasmon resonance (LSPR) response in the visible-near infrared region.
The LSPR response of WO2.72 is significantly improved, the thermal electron generation and carrier migration under long-wavelength light excitation is promoted, the lifetime of thermal electrons is extended, and the reaction rate and selectivity of hydrogen and benzaldehyde in photocatalytic oxidation of benzyl alcohol are improved.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to a tungsten oxide rod deposited gold particle coated cadmium sulfide material for selectively generating hydrogen and benzaldehyde by photocatalytic oxidation of benzyl alcohol, belonging to the field of nanomaterials and photocatalytic technology. Background Art
[0002] Photocatalytic technology has the potential to solve the environmental and energy crises, but traditional semiconductor-driven photocatalytic reactions are limited to being excited only by ultraviolet light, which makes them fail to achieve the desired effect. To address this problem, a commonly adopted strategy is to integrate semiconductor materials with plasmonic nanoparticles, and significantly improve the photocatalytic activity by utilizing the localized surface plasmon resonance (LSPR) effect unique to plasmonic nanoparticles. The hot electron injection mechanism is the key driving mechanism of the LSPR effect, that is, hot electrons can be generated under LSPR excitation, thereby initiating reactions on the surface of plasmonic nanoparticles or nearby semiconductors. The LSPR response of metal plasmonic nanoparticles is strong, but mainly in the visible light region. The absorption wavelength can also be extended by surface morphology modification, but excessive surface adsorption energy will hinder molecular reactions. In contrast, the LSPR response of non-metallic plasmonic nanoparticles is several orders of magnitude weaker, but by adjusting the dopant and vacancy concentrations, the LSPR response can be extended to the visible-near infrared (vis-NIR) region without affecting molecular reactions. WO 2.72 It is a representative non-metallic plasma material. It has the characteristics of weak LSPR response, but the LSPR response area can be controlled and adjusted. Therefore, improving WO 2.72 The LSPR response is the key to the photocatalytic activity of this material system.
[0003] Combining two independent plasmonic metal nanoparticles to induce plasmon coupling is an effective strategy to achieve enhanced LSPR response. Based on this, the present invention selectively deposits plasmonic metal nanoparticles on WO by a photodeposition method. 2.72 Gold (Au) nanoparticles are deposited on the tip of the nanorods. The introduction of Au particles can enhance the 2.72 The rods have an LSPR response in the vis-NIR region, which effectively promotes the generation of hot electrons under LSPR excitation by long-wavelength light. 2.72 A thin layer of cadmium sulfide (CdS) is applied to the surface to 2.72 The hot electrons generated by the excitation are extracted into the CdS layer, which significantly prolongs their lifetime for further reactions. In addition, the introduction of the CdS layer also leads to the 2.72 The formation of an S-type heterojunction between WO and CdS allows more efficient interband excitation of UV light. 2.72-Au / CdS composite material as a full-spectrum responsive photocatalyst catalytically oxidizes benzyl alcohol under simulated solar light excitation, with high hydrogen and benzaldehyde reaction rates and nearly 100% benzaldehyde selectivity. Summary of the invention
[0004] The present invention uses a photodeposition method to deposit Au nanoparticles on WO 2.72 Rod tip, first solvothermal synthesis of WO 2.72 Nanorods are prepared, and ethanol and water are added as dispersants, and finally a gold aqueous solution is added to deposit under light. After the deposition is completed, a CdS layer is coated on the outer layer of the nanorods by a water bath method to obtain a composite catalyst with full spectrum response.
[0005] WCl6 (0.12 g) was dissolved in 60 mL of cyclohexanol under stirring to form a transparent yellow solution. The obtained yellow solution was then transferred to a Teflon-lined stainless steel autoclave and heated at 200 °C for 6 h. The blue flocculent precipitate was collected by centrifugation, purified three times with anhydrous ethanol and deionized water, and dried completely at 60 °C in vacuum to obtain WO. 2.72 Nanorods.
[0006] The present invention relates to the construction of WO 2.72 Nanorods deposited Au particles (WO 2.72 NR-Au) is as follows: 20 mgWO 2.72 The nanorods were dispersed in a mixed solution of 10 mL of deionized water and 10 mL of ethanol, and then 100 μL of HAuCl4 aqueous solution (25 mM) was added. The mixture was stirred for 15 min in the dark. Subsequently, the dispersion was irradiated under a 300 W Xe lamp (full spectrum) for 30 min to obtain WO 2.72 Finally, the products were collected by centrifugation, washed with deionized water and anhydrous ethanol for three times, and then dried in a vacuum oven at 60 °C overnight.
[0007] The present invention relates to the construction of WO 2.72 NR-Au coated CdS layer (WO 2.72 NR-Au / CdS) method is as follows: 10 mgWO 2.72 NR-Au was dissolved in a round-bottom flask (200 mL) filled with 50 mL of deionized water. Subsequently, 1.5 mL of sodium citrate aqueous solution (0.1 M) and 2.5 mL of CdCl2 aqueous solution (0.05 M) were added in sequence. Stir for 5 min to mix them evenly. Then, 350 µL of concentrated ammonia (NH3·H2O, 28%) and 0.65 mL of thiourea aqueous solution (0.2 M) were added in sequence, and magnetic stirring was performed at 60 °C for 4.5 h to promote WO 2.72Formation of NR-Au / CdS The product was collected by centrifugation, washed with deionized water and anhydrous ethanol three times, and then dried in a vacuum oven at 60 °C overnight.
[0008] Tungsten trioxide is used as a non-metallic plasma semiconductor. By adjusting the vacancy concentration, its LSPR response is extended to the visible-near infrared region, effectively capturing long-wavelength sunlight and improving the absorption and utilization rate of sunlight.
[0009] Through WO 2.72 Au NPs were deposited on the top of NR, and the LSPR effects of the two materials achieved the best synergistic effect. 2.72 A strong electromagnetic field is generated around the NR-Au interface, which promotes the migration of carriers and the generation of hot electrons.
[0010] Adopted in WO 2.72 A thin layer of cadmium sulfide is coated on NR-Au to form a core-shell structure. This core-shell structure establishes an effective built-in electric field to 2.72 The hot electrons generated on NR are further extracted to the CdS layer, which significantly prolongs the lifetime of hot electrons. In addition, the introduction of the CdS layer also leads to the 2.72 The formation of an S-type heterojunction between NdFeB and CdS allows for more efficient interband excitation by UV light. Specific implementation plan
[0011] The present invention will be described in more detail below through specific embodiments, but the protection scope of the present invention is not limited to these embodiments.
[0012] Example 1 WO 2.72 Synthesis of NR WCl6 (0.12 g) was dissolved in 60 mL of cyclohexanol under stirring to form a transparent yellow solution. The obtained yellow solution was then transferred to a Teflon-lined stainless steel autoclave and heated at 200 °C for 6 h. The blue flocculent precipitate was collected by centrifugation, purified three times with anhydrous ethanol and deionized water, and dried completely at 60 °C in vacuum to obtain WO. 2.72 Nanorods.
[0013] Example 2 WO 2.72 NR deposited Au nanoparticles (WO 2.72 Synthesis of NR-Au 20 mg WO 2.72The nanorods were dispersed in a mixed solution of 10 mL of deionized water and 10 mL of ethanol, and then 100 μL of HAuCl4 aqueous solution (25 mM) was added. The mixture was stirred for 15 min in the dark. Subsequently, the dispersion was irradiated under a 300 W Xe lamp (full spectrum) for 30 min to obtain WO 2.72 Finally, the products were collected by centrifugation, washed with deionized water and anhydrous ethanol for three times, and then dried in a vacuum oven at 60 °C overnight.
[0014] Example 3 WO 2.72 NR-Au coated with CdS(WO 2.72 Synthesis of NR-Au / CdS 10 mg WO 2.72 NR-Au was dissolved in a round-bottom flask (200 mL) filled with 50 mL of deionized water. Subsequently, 1.5 mL of sodium citrate aqueous solution (0.1 M) and 2.5 mL of CdCl2 aqueous solution (0.05 M) were added in sequence. Stir for 5 min to mix them evenly. Then, 350 µL of concentrated ammonia (NH3·H2O, 28%) and 0.65 mL of thiourea aqueous solution (0.2 M) were added in sequence, and magnetic stirring was performed at 60 °C for 4.5 h to promote WO 2.72 Formation of NR-Au / CdS The product was collected by centrifugation, washed with deionized water and anhydrous ethanol three times, and then dried in a vacuum oven at 60 °C overnight.
[0015] Comparative Example 1 WO 2.72 Synthesis of NR coated with CdS layer (WO2.72NR / CdS) 10 mg WO 2.72 NR was dissolved in a round-bottom flask (200 mL) filled with 50 mL of deionized water. Subsequently, 1.5 mL of sodium citrate aqueous solution (0.1 M) and 2.5 mL of CdCl2 aqueous solution (0.05 M) were added in sequence. Stir for 5 min to mix them evenly. Then, 350 µL of concentrated ammonia (NH3·H2O, 28%) and 0.65 mL of thiourea aqueous solution (0.2 M) were added in sequence, and magnetic stirring was performed at 60 °C for 4.5 h to promote WO 2.72 Formation of NR-Au / CdS The product was collected by centrifugation, washed with deionized water and anhydrous ethanol three times, and then dried in a vacuum oven at 60 °C overnight.
[0016] Comparative Example 2 WO 2.72 Synthesis of NR-deposited Pt nanoparticles coated with CdS layer (WO2.72NR-Pt / CdS) 20 mg WO 2.72 The nanorods were dispersed in a mixed solution of 10 mL of deionized water and 10 mL of ethanol, and then 100 μL of H2PtCl6 aqueous solution (25 mM, 5% Pt loading) was added. The mixture was stirred for 15 min in the dark. Subsequently, the dispersion was irradiated under a 300 W Xe lamp (full spectrum) for 30 min to obtain WO 2.72 NR-Pt. Finally, the product was collected by centrifugation, washed with deionized water and anhydrous ethanol three times, and then dried in a vacuum oven at 60 °C overnight. 2.72 NR was dissolved in a round-bottom flask (200 mL) filled with 50 mL of deionized water. Subsequently, 1.5 mL of sodium citrate aqueous solution (0.1 M) and 2.5 mL of CdCl2 aqueous solution (0.05 M) were added in sequence. Stir for 5 min to mix evenly. Then, 350 µL of concentrated ammonia (NH3·H2O, 28%) and 0.65 mL of thiourea aqueous solution (0.2 M) were added in sequence, and magnetic stirring was performed at 60 °C for 4.5 h to promote WO 2.72 Formation of NR-Pt / CdS The product was collected by centrifugation, washed with deionized water and anhydrous ethanol three times, and then dried in a vacuum oven at 60 °C overnight.
[0017] The activity investigation method of the photocatalytic benzyl alcohol oxidation provided by the present invention is as follows: The photocatalytic benzyl alcohol oxidation reaction was carried out using a fully automatic online trace gas analysis system (Labsolar-6A). First, 5 mg of the photocatalyst was dispersed in 100 mL of an aqueous solution of benzyl alcohol (0.1 M) under magnetic stirring. The mixture was then transferred to a reactor (with a quartz cover) connected to a closed gas circulation and exhaust system. A 300 W xenon lamp was used as the light source and equipped with a standard AM1.5 filter. The temperature was maintained at 5 °C using circulating water. Prior to light irradiation, the reactor was evacuated for 15 minutes to remove any residual air. The generation of H2 was analyzed by a gas chromatograph equipped with a thermal conductivity detector (TCD) and a 5Å molecular sieve column using argon as the carrier gas. After the reaction was completed, the liquid product was analyzed using another gas chromatograph. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 a is the tungsten trioxide nanorod (WO 2.72 NR), the length is 1020±190 nm and the width is 110±19 nm. Figure 1 b and Figure 1 c are respectively WO in Example 2 2.72The TEM and HRTEM images of NR-Au clearly show the deposition of Au particles, and most of the gold particles are deposited on the tips of the nanorods. Figure 1 The lattice fringes of 0.38 nm and 0.20 nm shown in c correspond to WO 2.72 (010) crystal plane of NR and (200) crystal plane of Au nanoparticles. Figure 1 d is WO in Example 3 2.72 HRTEM image of NR-Au / CdS. The lattice fringes of 0.32 nm and 0.38 nm observed in the image correspond to the (002) crystal plane of CdS and WO, respectively. 2.72 (010) crystal plane of NR. Figure 1 e is the XRD diagram of different samples, WO 2.72 The characteristic peaks of NR, Au nanoparticles and CdS are consistent with the standard cards and the characterization results of HRTEM images, indicating that the samples were successfully prepared. Figure 1 g is the UV-visible diffuse reflectance spectrum of the sample, WO 2.72 -Au composites show Au nanoparticles and WO in the 600-800 nm region. 2.72 The strong absorption that is not found in nanorods indicates that WO 2.72 -The absorption spectrum of Au is not Au particles and WO 2.72 Simple summation of the absorption spectra of nanorods. After coating with CdS layer, the characteristic Au peak red-shifts. Although a small part of oxygen vacancies may disappear in this process, WO 2.72 -Au / CdS composites are still plasmonically active and give broad absorption in the visible and NIR regions. Figure 1 The electron paramagnetic resonance (EPR) characterization results of f are consistent with the observations, that is, at g = 2.001, WO 2.72 -The oxygen vacancy signal of Au / CdS is slightly lower than that of WO 2.72 NR.
[0019] Figure 2 a and Figure 2 b is WO 2.72 NR, WO 2.72 NR / CdS、WO 2.72 The XPS graphs of W 4f and O 1s of NR-Au / CdS further confirm the existence of oxygen vacancies by observing low-valence W species and oxygen defect signals. Figure 2 The W4f XPS images of a represent W 6+ , W 5+ , W 4+ The three W species can be found in Figure 2The peaks representing lattice oxygen, oxygen defects and adsorbed oxygen were observed in the O1s XPS graph of b. It is worth noting that after coating with the CdS layer, the peaks corresponding to W4f and O1s shifted to lower binding energies. Figure 2 c and Figure 2 d is CdS, WO 2.72 NR / CdS、WO 2.72 XPS graphs of Cd 3d and S2p of NR-Au / CdS. 2.72 NR / CdS and WO 2.72 The Cd 3d and S 2p peaks of NR-Au / CdS shift to higher binding energy regions than those of pure CdS, indicating that electrons migrate from CdS to WO upon contact. 2.72 NR. This is in CdS and WO 2.72 An interfacial electric field is generated between them, which is the characteristic of the formation of an S-type heterojunction. Figure 2 (eh) is WO 2.72 In situ XPS graphs of W4f, O 1s, Cd 3d, and S 2p of NR-Au / CdS in the dark and under light conditions. Figure 2 e shows that the W 4f peak shifts to a higher binding energy region, while Figure 2 f Cd 3d and Figure 2 The S 2p peak of g shifts to the low binding energy region, further confirming the formation of the S-type heterojunction.
[0020] Figure 3 a and Figure 3 b is a graph showing the H2 production and H2 generation rate of different photocatalysts under different illumination times. Under the excitation of a 300W Xe lamp, the WO in Example 1 2.72 The hydrogen generation activity of the NR sample is almost inactive, while the WO in Example 2 after the deposition of Au nanoparticles 2.72 In the NR-Au sample, the activity change is still not obvious, and the hydrogen evolution yield and rate do not change much. However, after the cadmium sulfide layer is grown, the WO in Example 3 2.72 In the NR-Au / CdS sample, it can be observed that the hydrogen evolution activity is significantly enhanced, and the activity is higher than that of WO in Comparative Example 1. 2.72 NR / CdS and WO in Comparative Example 2 2.72 The NR-Pt / CdS sample is stronger. Under the optimal conditions, WO 2.72 -The maximum activity of Au / CdS can reach 165.5 mmol g -1 h -1 . Figure 3 c and Figure 3 d is WO 2.72 NR / CdS and WO 2.72Apparent quantum yield (AQY) of NR-Au / CdS at different wavelengths. As can be seen from the figure, at the same wavelength, WO 2.72 The AQY of NR-Au / CdS exceeds that of WO 2.72 NR / CdS, and WO at 420nm 2.72 The AQY of NR-Au / CdS reaches an astonishing 37%.
[0021] Figure 4 It is a study of charge dynamics using femtosecond transient absorption spectroscopy (fs-TAS) technology. Figure 4 a and Figure 4 b is WO under 380 nm pump laser 2.72 NR / CdS and WO 2.72 Two-dimensional fs-TAS image of NR-Au / CdS. Figure 4 e and Figure 4 f is the various transient absorption signal diagrams of the two materials under 380nm excitation. Figure 4 a and Figure 4 b WO was observed at 445 nm 2.72 Ground state bleaching (GSB) signal of NR. Figure 4 i and Figure 4 j are the GSB signal decay kinetics fitting curves of the two materials at 445 nm. 2.72 NR / CdS and WO 2.72 The average lifetimes of GSB signals of NR-Au / CdS are 381.6ps and 240.5ps, respectively. 2.72 The average lifetime of the GSB signal of NR-Au / CdS is shorter than that of WO 2.72 The NR-CdS is shorter, indicating that the presence of Au can promote the transfer of carriers between WO2.72NR and CdS. Figure 4 c and Figure 4 d is the two-dimensional fs-TAS image of the two materials under 700nm pump laser. Figure 4 g and Figure 4 h is a graph of various transient absorption signals of the two materials under 700nm excitation. Figure 4 c and Figure 4 d (GSB) signal of CdS observed at 500 nm. Figure 4 k and Figure 4 l is the GSB signal decay kinetics fitting curve of the two materials at 500 nm. Figure 4 i and Figure 4 The results of j are the same, WO 2.72 The average lifetime of the GSB signal of NR-Au / CdS is shorter than that of WO 2.72The shorter one of NR-CdS indicates that the presence of Au can promote the high-energy electrons to 2.72 Transfer of NR to CdS.
[0022] Figure 5 a is WO 2.72 The hydrogen evolution performance of NR-Au / CdS in pure benzyl alcohol (BA) and after adding water shows that the catalyst exhibits good photocatalytic activity in BA aqueous solution, while the activity in pure BA is not significant. This indicates that the free radicals generated in the aqueous solution must play a key role in the photocatalytic redox coupling reaction. Figure 5 b and Figure 5 c respectively WO 2.72 In situ EPR spectra of NR-Au / CdS in pure BA and in a system containing both BA and water, no EPR signal was observed without light irradiation, but carbon-centered free radical signals were observed after irradiation. Figure 5 The hydroxyl radical (‧OH) signal was also observed in c, which is consistent with Figure 5 a phenomenon is consistent. Figure 5 d is the WO after adding different scavengers 2.72 H2 and benzaldehyde (BAD) yields of NR-Au / CdS, with a control experiment in which isopropyl alcohol (IPA) was added as a ‧OH radical scavenger. As expected, the production activity of BAD was significantly inhibited in the presence of IPA. In addition, since ‧OH is produced by the oxidation of hydroxyl ions by photogenerated holes, a control experiment was performed using sodium oxalate (SO) to scavenge photogenerated holes. After the addition of SO, the production activity of BAD was further inhibited, indicating that the ‧OH radical plays a key role in the selective oxidation of BA. Figure 5 e is WO 2.72 In situ DRIFTS spectrum of NR-Au / CdS after illumination at 1710 cm −1 Around 1350 cm, the characteristic stretching vibration signal of C═O bond begins to appear, and its intensity increases with time. −1 An inverted peak was observed at , corresponding to the original COH bond, indicating that BA was continuously converted to BAD under light irradiation. Figure 5 f pure BA in WO 2.72 In situ FTIR spectroscopy of NR-Au / CdS revealed that no C═O stretching vibration signal was detected when the reaction was carried out in pure BA, again emphasizing the importance of ‧OH in this process.
[0023] The above experimental results prove that the tungsten oxide rod deposited gold particles coated cadmium sulfide material we synthesized has high carrier separation efficiency and high-energy electron utilization, as well as excellent photocatalytic selective benzyl alcohol oxidation and hydrogen evolution performance.
[0024] Although the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention.
Claims
1. A method for preparing cadmium sulfide coated with gold particles deposited on tungsten oxide rods for photocatalytic selective oxidation of benzyl alcohol for hydrogen evolution, characterized in that Solvothermal method for preparing WO 2.72 NR was used as a deposition carrier, and then HAuCl4·3H2O was added to reduce gold ions to gold nanoparticles under light and selectively deposit WO 2.72 NR tip, and finally coated with WO on which gold nanoparticles were deposited by water bath method 2.72 NR, get WO 2.72 NR-Au / CdS composite material; the prepared material has a wide spectral response characteristic, high carrier separation efficiency and hot electron utilization rate, and exhibits excellent photocatalytic benzyl alcohol hydrogen evolution performance; specifically comprises the following steps: Step 1: Under stirring conditions, WCl6 (0.12 g) was dissolved in 60 mL of cyclohexanol and ultrasonicated to form a transparent yellow solution; the obtained yellow solution was then transferred to a Teflon-lined stainless steel autoclave and heated at 200 °C for 6 h; the blue flocculent precipitate was collected by centrifugation, purified three times with anhydrous ethanol and deionized water, and dried completely under vacuum at 60 °C to obtain WO 2.72 Nanorods; Step 2: 20 mg WO 2.72 The nanorods were dispersed in a mixed solution of 10 mL of deionized water and 10 mL of ethanol, and then 100 μL of HAuCl4 aqueous solution (25 mM) was added; the mixture was stirred for 15 min in the dark; subsequently, the dispersion was irradiated under a 300 W Xe lamp (full spectrum) for 30 min to obtain WO 2.72 NR-Au; Finally, the product was collected by centrifugation, washed three times with deionized water and anhydrous ethanol, and then dried in a vacuum oven at 60 °C overnight; Step 3: 10 mg WO 2.72 NR-Au was dissolved in a round-bottom flask (200 mL) filled with 50 mL of deionized water. Subsequently, 1.5 mL of sodium citrate aqueous solution (0.1 M) and 2.5 mL of CdCl2 aqueous solution (0.05 M) were added in sequence. The mixture was stirred for 5 min to mix evenly. Then, 350 µL of concentrated ammonia (NH3·H2O, 28%) and 0.65 mL of thiourea aqueous solution (0.2 M) were added in sequence. The mixture was magnetically stirred at 60 °C for 4.5 h to promote the WO 2.72 Formation of NR-Au / CdS; the product was collected by centrifugation, washed three times with deionized water and anhydrous ethanol, and then dried in a vacuum oven at 60°C overnight.
2. The method for preparing cadmium sulfide coated with gold particles deposited on tungsten oxide rods according to claim 1, characterized in that: The tungsten hexachloride in the first step is very easy to deliquesce and needs to be stored in a dry place to prevent deterioration.
3. The method for preparing cadmium sulfide coated with gold particles deposited on tungsten oxide rods according to claim 1, characterized in that: The theoretical weight ratio of the gold particles loaded with the amount of chloroauric acid trihydrate added in the second step is 5%.
4. The method for preparing tungsten oxide rod deposited gold particles coated with cadmium sulfide according to claim 1, characterized in that: In the third step, the morphology of the cadmium sulfide layer is easy to change. The setting values of different water baths are different from the theoretical values. It is advisable to keep the same water bath during the experiment.
5. The method for preparing cadmium sulfide coated with gold particles deposited on tungsten oxide rods according to claim 1, characterized in that: The water bath time of the cadmium sulfide layer in the third step is only for reference, and the thickness of the cadmium sulfide layer is different at different water bath times.
Citation Information
Patent Citations
Nano-precious metal modified tungsten oxide photocatalytic coating and its preparation method
CN102268198A
Method for preparing benzaldehyde through catalytic oxidation of benzyl alcohol by polyoxometallate
CN111662169A